6x2 + 7x = 5
6x2 + 7x - 5 = 0
x =[ -7 ± √[72 - 4(6)(-5)] ]/2(6)
x = [-7 ± √(49 + 120)]/12
x = (-7 ± √ 169)/12
x = (-7 ± 13)/12
x = (-7 + 13)/12 or x = (-7 - 13)/12
x = 6/12 = 1/2 or
x = -20/12 = - 5/3
It is -9x plus 5.
4x - 7 = 5 + 7x x = -4
6x + 8 = 13, 6x = 13 - 8, 6x = 5, x = 5/6
x = 8
6x + 3 = 2x + 5 4x = 2 x=1/2
Given 6x + (7x-8) = -5 6x + 7x - 8 = -5 ==> 13x = 3 therefore, x = 3/13
X=2
-8 + 7(6x) + 3 = -7x - 5 - 1-8 + 42x + 3 = -7x - 5 - 142x - 8 + 3 = -7x - 5 + (-1)42x - 5 = - 7x - 642x + 7x - 5 + 5 = - 7x + 7x - 6 + 549x = -149x/49 = -1/49x = -1/49
It is an expression that can be simplified to: 9-13x
7x-9
6x - 12 + 4x + 5 = 06x + 4x = 12 - 510x = 7x = 7/10
It is -9x plus 5.
(7x-3)(2x+5) 14x2 + 29x - 15, write 29x = 35x - 6x = 14x2 - 6x + 35x - 15 = (14x2 - 6x) + (35x - 15) = 2x(7x - 3) + 5(7x - 3) = (7x-3)(2x+5)
-7x + 5 = -9 -7x = -14 7x = 14 x = 2
7x = 5+5x 7x-5x = 5 2x = 5 x = 2.5
y=(6x-5)/3
If (6x-5) and (-x+9) are both equal to 'y', then they must beequal to each other, and you can say that6x - 5 = -x + 9Now add 'x' to each side:7x - 5 = 9Add 5 to each side:7x = 14Divide each side by 7:x = 2y = 7